The effect of levosimendan on myocardial ischemia–reperfusion injury in streptozotocin-induced diabetic rats - Kiraz, Hasan Ali (Libyan J Med, 2015)
OBJECTIVE: Ischemia/reperfusion (I/R) injury is an important cause of myocardial damage by means of oxidative, inflammatory, and apoptotic mechanisms. The aim of the present study was to examine the potential cardio protective effects of levosimendan in a diabetic rat model of myocardial I/R injury. METHODS: A total of 18 streptozotocin-induced diabetic Wistar Albino rats (55 mg/kg) were randomly divided into three equal groups as follows: the diabetic I/R group (DIR) in which myocardial I/R was induced following left thoracotomy, by ligating the left anterior descending coronary artery for 60 min, followed by 2 h of reperfusion; the diabetic I/R levosimendan group (DIRL), which underwent I/R by the same method while taking levosimendan intraperitoneal 12 µg kg(−1); and the diabetic control group (DC) which underwent sham operations without tightening of the coronary sutures. As a control group (C), six healthy age-matched Wistar Albino rats underwent sham operations similar to the DC group. Two hours after the operation, the rats were sacrificed and the myocardial tissue samples were examined by light microscopy for evidence of myonecrosis and inflammatory cell infiltration. RESULTS: Myonecrosis findings were significantly different among groups (p=0.008). Myonecrosis was more pronounced in the DIR group compared with the C, DC, and DIRL groups (p=0.001, p=0.007 and p=0.037, respectively). Similarly, the degree of inflammatory cell infiltration showed significant difference among groups (p<0.0001). Compared with C, DC, and DIRL groups, the inflammatory cell infiltration was significantly higher among the DIR group (p<0.0001, p<0.0001, and p=0.020, respectively). Also, myocardial tissue edema was significantly different among groups (p=0.006). The light microscopic myocardial tissue edema levels were significantly higher in the DIR group than the C, DC, and DIRL groups (p=0.001, p=0.037, and p=0.014, respectively). CONCLUSION: Taken together, our data indicate that levosimendan may be helpful in reducing myocardial necrosis, myocardial inflammation, and myocardial tissue edema resulting from ischemia–reperfusion injury.